Haberman Star Teacher Interview as a predictor of success in urban teacher preparation - Jennifer H. Waddell; Jacob M. Marszalek (Arizona State University, 2018)
In urban schools, along with skills for effective teaching, successful teachers must also possess values and belief systems conducive to teaching effectively in diverse settings (Becker, Kennedy, Hundersmarck, 2003; Haberman, 2008; Metzgar Wu, 2008). As demonstrated in CAEP standard 3, there is a critical need for EPPs to admit candidates who have both the dispositions to be effective teachers in urban schools and the propensity for success within the preparation program. The Haberman Star Teacher Interview is a commercial teacher selection instrument designed for use in selecting teachers for urban schools. This study examines the validity of the instrument as a selection instrument for teacher preparation programs. The selection instrument was administered to 109 students before entry into an urban teacher preparation program at an urban university in the U.S. Midwest. Inter-rater agreement and principle components analysis provided evidence of reliability and structural validity of the multi-part Haberman scores. Logistic regression analyses supported the validity of using the Haberman scores to predict later program attrition, but not in the manner recommended by its developers. Within this paper, the authors recommend the cautious use of the instrument in urban teacher preparation. Application of scoring and program implications are discussed.